The Types of Communication Accommodation Strategies in English as Foreign Language (EFL) Classrooms - Manuaba, Ida Bagus; Putra, I Nyoman Adi Jaya (LPPM Undiksha, 2021)
English is one of international language which is taught widely in various countries in the world. Entering millennial and industrial 4.0 era, English has important role as the function of English is as a tool or media to communicate with other countries and it is also as language of science, technology, social-economy, culture, and art. Communication Accommodation Theory which consists of communication accommodation strategies are very important to accommodate the students in teaching learning activity. This research aimed at analyses types of communication accommodation strategies are used by teacher when teaching Basic English and the motive of implementing communication accommodation strategies by the teacher Classroom Interactions. Subjects of this research were two the English teachers. This research was designed in qualitative research. The data were collected through voice recorder, interview and documentation. The data were analyzed qualitatively. The results of this study revealed that there were four strategies used in teaching learning process by the teacher such as approximation, interpretability, discourse management and emotional expression. Moreover, the teachers had some main motive to apply these strategies such as to make the students understand, give clear explanation to students and get the students’ attention.